Design and monitoring of an innovative geothermal system including an underground heat-storage tank. Issue 8 (20th June 2016) - Bonamente, Emanuele; Moretti, Elisa; Buratti, Cinzia; Cotana, Franco
ABSTRACT: The design, implementation, and setup of an innovative layout for geothermal heating and cooling systems are presented. An underground heat-storage tank, used as a thermal flywheel, decouples the utility side of the system (i.e., the heat pump) from the geothermal side (i.e., the boreholes). The innovative layout allows for a more efficient exploitation of the ground energy reservoir and a sensible reduction of investment costs. A pilot system has been realized for a commercial building near the city of Perugia, Italy. The design of the heat-storage tank, the heat exchangers, the monitoring system, and the operation modes were carefully studied. The heating performance monitoring shows that the innovative approach allows for a significant reduction of the ground heat exchangers, hence requiring for fewer and/or shorter boreholes (up to 75%) while still supplying the total energy need. The peak-power demand is covered taking advantage of the high thermal capacity of the water inside the tank, while the reduced-size geothermal boreholes are used with a higher duty cycle to independently provide the total energy need.